WIRAUSAHA PEREMPUAN PEMULA DI BIDANG KULINER MENGGUNAKAN TEKNOLOGI: DAMPAK DAN BERKAH COVID-19 - Rosa Prafitri Juniarti (ILIN Institute, 2020)
The Covid-19 pandemic has made many people learn and start new things in their lives, including women. Many women started entrepreneurship due to the Covid-19 Pandemic. Culinary becomes an attractive choice for starting a business because it is easy to begin and is a primary need. This study aims to determine how novice female entrepreneurs in the culinary field use technology in their business processes. This study used a qualitative method with a case study method. Data were collected through semi-structured interviews. The results showed that this startup woman entrepreneur carried out almost all of her business processes with the help of online media, especially WhatsApp. Simple marketing research activities, finding suppliers, preparing and conducting marketing communications, conducting transactions, doing co-creation and collaborating with partners are supported by online communication media. This study also seeks to capture the difficulties and challenges faced by women entrepreneurs in the culinary field. Because this research was conducted with a case study on five women entrepreneurs in the culinary field, further research can use quantitative methods and use a large sample.